Evaluation of the possibilities of shear wave elastography for differentiation of lymphomatous and reactive changes of superficial lymph nodes - E. V. Kovaleva; T. Yu. Danzanova; G. T. Sinyukova; E. A. Gudilina; P. I. Lepedatu; G. F. Allahverdieva; P. A. Zeynalova; V. B. Larionova; A. A. Semenova (Онкогематология)
Objective: to evaluate the possibilities of ultrasound elastography for differentiation of reactive and lymphomatous superficial lymph nodes (LN).Materials and methods. The prospective study included 138 patients with enlarged superficial LN. Based on a previous histological examination, patients were divided into two groups: 1st group (n = 108) – patients with non-Hodgkin’s lymphomas and Hodgkin’s lymphoma; 2nd (n = 30) – patients with reactive (inflammatory) changes in superficial LN. All patients underwent ultrasound elastography of the enlarged LN using ARFI technology.Results. According to the results of ultrasound elastography, the average, minimum, and maximum shear wave velocities for enlarged LN in lymphoma (1st group) were 2.616 ± 0.684; 1.980 ± 0.557 and 3.351 ± 0.987 m / s, respectively; for LN with reactive changes (2nd group) – 1.704 ± 0.223; 1.414 ± 0.209 and 2.027 ± 0.261 m / s, respectively. Thus, the average, minimum, and maximum values of shear wave velocities significantly different between the groups (p ˂0.001). The cut off values of the average shear wave velocity in the differential diagnosis of lymphoma and hyperplasia are determined at the level of 2.05 m / s, with a sensitivity of 88.5 %, specificity of 100 %, and AUC of 0.942 (p ˂0.001).Conclusion. Ultrasound elastography demonstrated statistically significant differences in shear wave velocity in the enlarged superficial LN in lymphoma and in inflammatory processes that can be used as a preliminary non-invasive differential diagnosis of enlarged superficial LN in these conditions.